Pengaruh Gaya Belajar Siswa Terhadap Konsep Pemahaman IPA SMP pada Siswa MTsN 1 Jember - Wilda Robiah Salsabila; Aditya Satya Utama; Vinna Nurdhini Islamy; Andri Juniaraju Putra; Firda Yanuarti Zahra; Ika Dewi Sumiati; Eka Puspita Kartika Sari (Jurnal Ilmiah Wahana Pendidikan, 2026)
Entering the 21st century, education is required to equip students with four key competencies, namely critical thinking, creativity, communication, and collaboration, so that they can adapt to the changing times. Science education is an important means of developing these skills, as it emphasizes critical thinking and understanding scientific concepts. However, the abstract nature of science material often poses a challenge for students in understanding and connecting theory with real life. This study aims to examine the effect of learning styles on science concept understanding among students at MTsN 1 Jember. The results of the observation show that there are variations in students' learning styles, including visual, auditory, and kinesthetic, which also affect their level of concept comprehension. Students who receive learning methods that suit their learning styles show better comprehension results. Therefore, teachers are expected to be able to apply flexible and diverse learning strategies by adjusting the methods, media, and learning activities to the characteristics of students' learning styles in order to improve the effectiveness and quality of science learning.